DEMOKRASI DAN PRAKTIK KONSERVATISME ORMAS KEAGAMAAN DI SUMATRA BARAT - Hairunnas Hairunnas; Afrizal Afrizal; Asrinaldi Asrinaldi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
This article discusses the practice of conservatism religious organizations in West Sumatra. After the implementation of regional autonomy law, various religious organizations appeared en masse with variations in the focus of the movement. The purpose of this study is to look at the practices and factors that cause conservatism by using the concept of religious conservatism as an analytical tool. This research uses qualitative research with a case study approach, data is collected by in-depth interview techniques and collection of documentation. The results of this study indicate that the practice of conservatism religious organizations in West Sumatra places the value of religious teachings on the traditions of the Prophets and Apostles with a rigid spirit of purification of the Qur'an and Sunnah. In practice, religious norms and cultural identities are the main instruments for the formation of morals and political attitudes. In addition, narratives based on religion and customs as ideological elements are considered fixed and final.Keywords: Religious Conservatism; Religious Organizations; Minangkabau AbstrakArtikel ini menjelaskan mengenai praktik konservatisme ormas keagamaan di Sumatra Barat. Pasca diberlakukan undang-undang otonomi daerah, berbagai ormas keagamaan bermunculan secara massif dengan variasi fokus gerakan. Tujuan dalam penelitian ini ingin melihat praktik dan faktor penyebab konservatisme dengan menggunakan konsep konservatisme agama sebagai pisau analisis. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus, data dikumpulkan dengan teknik wawancara mendalam, dan pengumpulan dokumentasi. Hasil penelitian ini menunjukkan praktik konservatisme ormas keagamaan di Sumatra Barat meletakan nilai ajaran agama pada tradisi masa Nabi dan Rasul dengan semangat pemurnian kembali kepada Alquran dan Sunnah secara kaku. Dalam praktiknya norma agama dan identitas kultural sebagai instrumen utama pembentukan moral dan sikap politik. Selain itu narasi berbasis keagamaan dan adat sebagai elemen ideologis yang dinilai sudah tetap dan final.Kata Kunci : Konservatisme Agama; Ormas Keagamaan; Minangkabau.